2022
DOI: 10.1166/jbmb.2022.2188
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drought Tolerant Rice Genotypes Based on Morpho-Physiological and Yield Traits Under Normal and Drought Stress Conditions

Abstract: Water shortage is a serious climatic factor that drastically limits rice productivity. Thereupon, the development of better adapting rice genotypes under water deficit stress is imperious to maintain rice yield to ensure food security worldwide. The current study focused on genetic variability of morpho-physiological traits of rice to discover relationships between morpho-physiological and yield contributing traits under drought stress conditions in 24 rice genotypes during 2019 and 2020 seasons. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…In our research, traits such as leaf proline content, flag leaf area, fresh shoot weight and spikelet fertility exhibited high heritability and high GAM. The outcomes inferred were in tune with the results observed by Ganapathy et al [10]; Mina et al [9]; [22][23][24] suggesting least amount of environmental influence indicating the prevalence of the additive gene effects. As a consequence, under water stress conditions, genotypes can be altered and chosen for these features to improve drought tolerance.…”
Section: Resultssupporting
confidence: 88%
“…In our research, traits such as leaf proline content, flag leaf area, fresh shoot weight and spikelet fertility exhibited high heritability and high GAM. The outcomes inferred were in tune with the results observed by Ganapathy et al [10]; Mina et al [9]; [22][23][24] suggesting least amount of environmental influence indicating the prevalence of the additive gene effects. As a consequence, under water stress conditions, genotypes can be altered and chosen for these features to improve drought tolerance.…”
Section: Resultssupporting
confidence: 88%
“…Significant and highly significant mean square estimates were recorded for genotypes, parents, crosses and the interaction among them for all these traits under both water deficit and normal conditions, except root/shoot ratio under both conditions for all sources of variance, chlorophyll content and relative water content under water deficit and 1000-grain weight under normal condition for parents vs. crosses which were insignificant. These results agree with those obtained by Saleem et al, (2010), El-Hity et al, (2015, Daher (2018), Abdelaty et al, (2022) and Hassan et al, (2023). Estimates of both general (GCA) and specific combining ability (SCA) variances were found to be highly significant for all root traits, yield and its components and some physiological traits under both water deficit and normal irrigation conditions, except root/shoot ratio under both conditions and root length for testers under water deficit condition which were insignificant, indicating the importance of additive and non-additive genetic variances in determining the inheritance of these studied traits.…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…There are 34 million ha of rainfed rice fields and 8 million ha of upland rice fields troubled by drought stress [19]. This abiotic stress can occur during rice development [20], for instance, in seedlings, where it causes improper growth and decreased yield [21]. Some investigations found that drought stress negatively affected the germination phase, seed vigor, photosynthesis activity, leaf membrane stability and osmotic content [22,23].…”
Section: Introductionmentioning
confidence: 99%